PENGARUH DOPING TEMBAGA TERHADAP SUSEPTIBILITAS MAGNETIK DAN KOMPOSISI SERTA SIFAT KRISTALINITAS PASIR ALAM SUNGAI ROKAN DIPREPARASI DENGAN METODE BALL MILLING - Salomo Salomo; Nanda Rizki Yosefi (Komunikasi Fisika Indonesia, 2022)
The effect of copper doping on magnetic susceptibility and composition and crystallinity properties of Rokan River natural sand has been investigated. Before going through the ball milling (BM) process, the natural sand has been processed using an iron sand separator (ISS) and neodynium iron boron (NdFeb) magnets to separate magnetic and non-magnetic particles, so the result is called an ISS product. The ISS product is crushed through a BM process for 70 hours, and the result is called BM 1 product. Furthermore, BM 1 is divided into 3 parts and then doped with copper (Cu) with a concentration of 0 gr; 5 gr; and 10 gr using BM for 30 hours and are called BM 2A, BM 2B, and BM 2C products, respectively. BM 2A, BM 2B, and BM 2C products were identified and characterized using x-ray flourescence (XRF) and x-ray diffraction (XRD). XRF identification results showed that the composition of copper elements increased from 0.015% to 37.874%. Meanwhile, Fe elements decreased and other elements such as Al, Si, P, K, Ti, V, Cr, Ca and Mn as well. The XRD test results for BM 2A, BM 2B, and BM 2C products produced a hematite (Fe2O3) phase with a hexagonal crystal structure. The crystal size was calculated using the Scherrer Equation where the average crystal size decreased by 26,137 nm; 25,501 nm; and 25.270 nm.